Comparison and Characterization of the Structure and Physicochemical Properties of Three Citrus Fibers: Effect of Ball Milling Treatment - Zhanmei Jiang; Minghan Zhang; Yuxuan Huang; Chenglong Ma; Sinan Mu; Hongyu Li; Xianqi Liu; Yue Ma; Yue Liu; Juncai Hou (Foods, 2022)
Effects of ball milling (BM) on the structure and physicochemical properties of three types of citrus fibers were investigated. With the extension of the grinding time, the particle size of citrus fibers significantly decreased. Fourier transform infrared spectroscopy (FTIR) showed that the three citrus fibers had similar chemical groups, and more -OH and phenolic acid groups were exposed after BM, and pectin and lignin were not degraded. Scanning electron microscope (SEM) results showed that the appearance of particles changed from spherical to fragmented, irregular shapes. The water holding capacity (WHC), oil holding capacity (OHC), and water swelling capacity (WSC) of citrus fibers LM, JK, and FS reached the maximum value after BM of 2 h (increasing by 18.5%), 4 h (increasing by 46.1%), and 10 h (increasing by 38.3%), respectively. After 10 h BM, citrus fibers FS and JK had the highest adsorption capacity of cholesterol and sodium cholate, increasing by 48.3% and 48.6%, respectively. This indicates that BM transforms the spatial structure of citrus fibers and improves their physicochemical properties.